Changes in REM-sleep percentage over the adult lifespan - Floyd, Judith A; Janisse, James J; Jenuwine, Elizabeth S; Ager, Joel W (Sleep (New York, N.Y.), 2007)
To resolve inconsistencies in previously reported changes in percentage of rapid eye movement sleep (REM%) over the adult lifespan and to identify gaps in available information about adults' REM sleep. A research synthesis approach specifically designed to detect nonlinear change. Cubic B smoothing splines were fitted to scatterplots generated from reported means and variance for REM%, REM minutes, and total sleep time. 382 English-language research reports provided REM% values for 4171 subjects; REM minutes values for 2722 subjects; and values of total sleep time for 5037 subjects. Samples were composed of subjects described by authors as normal or healthy. Mean ages of samples ranged from 18.0 to 91.7 years. University research center. N/A. Two coders extracted information. Intercoder reliability was above cutoffs for excellent. Authors often failed to describe screening procedures used to determine subjects' health status. Few results were reported separately for women. The functional relationship between age and REM% was essentially linear over much of the adult lifespan, decreasing about 0.6% per decade. The best estimate of when REM% ceased its small linear decline was the mid-70s, after which time a small increase in REM% was observed due to REM minutes increasing while total sleep time declined. Ability to detect both linear and nonlinear change in REM%, REM minutes, and total sleep time over the lifespan was useful for resolving inconsistent findings about the existence of changes in REM% with aging. This approach to research synthesis also facilitated identification of ages for which little normative information about REM sleep was available.